Law Protection And Criminal Responsibility Of Land Deed Official (PPAT) On The Deed He Made - Fajar Fitrio Dwi Nugroho; Amin Purnawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze the responsibility of PPAT, the precautionary principle and law protection of PPAT on deed made (case study in State Court of Salatiga Decision 43 /Pdt.G/2017/PN. Slt). The approach used in this study is a sociological juridical methods with specifications this study uses descriptive analytical type. Data collection techniques using primary data through interviews and secondary data is by doing an inventory of the literature books, documents, articles. Qualitative analysis techniques. The results show based protection against PPAT, PPAT entitled to legal protection such as safety, both in mind and physical harassment and threats from others. PPAT parties responsible for the deed he made that is in accordance with the rules and principles PPAT deed and responsible to attend the hearing. Based on the precautionary principle PPAT less cautious in making payment of the memorandum of land. The results show based protection against PPAT, PPAT entitled to legal protection such as safety, both in mind and physical harassment and threats from others. PPAT parties responsible for the deed he made that is in accordance with the rules and principles PPAT deed and responsible to attend the hearing. Based on the precautionary principle PPAT less cautious in making payment of the memorandum of land. The results show based protection against PPAT, PPAT entitled to legal protection such as safety, both in mind and physical harassment and threats from others. PPAT parties responsible for the deed he made that is in accordance with the rules and principles PPAT deed and responsible to attend the hearing. Based on the precautionary principle PPAT less cautious in making payment of the memorandum of land.Keywords: PPAT; Legal Protection; PPAT Responsibility; Precautionary Principle.